Increasing the Learning Motivation of Class V Students through the Application of Crossword Puzzles - Yasa, Arnelia Dwi; Kartika, Annisa Cholilaya; Muzakir, Fathol (Actual Insight, 2025)
This research aims to improve the learning motivation of grade V elementary school students through the application of crossword puzzle media in Pancasila Education learning. The method employed is Classroom Action Research (CAR) using the Kemmis and McTaggart model, which is conducted in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. Data were collected through learning motivation questionnaires administered during the pre-cycle, first cycle, and second cycle. The research results showed a gradual and significant increase in students' learning motivation after the use of crossword puzzle media. The average learning motivation score improved from 1.87 (46.75%) in the pre-cycle to 2.25 (56.25%) in the first cycle, and further increased to 2.87 (71.75%) in the second cycle. Learning activities became more active, enjoyable, and collaborative, encouraging students to participate actively and work together in completing learning tasks. The provision of varied learning media, engaging activities, and constructive feedback also played an important role in enhancing students' motivation and involvement. The use of crossword puzzle media proved to be effective in fostering critical thinking, strengthening students’ active participation, and creating positive interactions among students throughout the learning process. Based on these findings, crossword puzzle media is recommended as an alternative innovative learning strategy that teachers can implement, particularly in Pancasila Education learning at the elementary school level, to improve students' motivation and learning outcomes.